USE OF WATER RESOURCES TO SUPPLY ELECTRICITY TO REMOTE AREAS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This work highlights the possibilieties of using small water sources in the Bulokbashi and Kurgantepe districts of the Andijan region to provide electricity using small hydropower plants in remote areas. Also provides an analysis of information useful for the use of some types of small hydropower plants.